The role of cellular iron deficiency in controlling iron export - Link, Camille; Knopf, Julia Daniela; Marques, Oriana; Lemberg, Marius; Muckenthaler, Martina (Biochimica et biophysica acta. General subjects, 2021)
Background - Iron export via the transport protein ferroportin (Fpn) plays a critical role in the regulation of dietary iron absorption and iron recycling in macrophages. Fpn plasma membrane expression is controlled by the hepatic iron-regulated hormone hepcidin in response to high iron availability and inflammation. Hepcidin binds to the central cavity of the Fpn transporter to block iron export either directly or by inducing Fpn internalization and lysosomal degradation. Here, we investigated whether iron deficiency affects Fpn protein turnover. - Methods - We ectopically expressed Fpn in HeLa cells and used cycloheximide chase experiments to study basal and hepcidin-induced Fpn degradation under extracellular and intracellular iron deficiency. - Conclusions/General significance - We show that iron deficiency does not affect basal Fpn turnover but causes a significant delay in hepcidin-induced degradation when cytosolic iron levels are low. These data have important mechanistic implications supporting the hypothesis that iron export is required for efficient targeting of Fpn by hepcidin. Additionally, we show that Fpn degradation is not involved in protecting cells from intracellular iron deficiency.
Gesehen am 12.05.2021
First published: 16 December 2020